Proposed Business Process Management (BPM) Tools for Optimizing Business Process Management at PT Hutama Karya Infrastruktur - Ratna Dwi Astuti (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2026)
This study aims to develop and apply a governance-oriented Business Process Management (BPM) tool selection framework for PT Hutama Karya Infrastruktur, a project-based infrastructure enterprise undergoing digital transformation in Indonesia. A mixed-methods design was employed by combining internal gap analysis, Business Model Canvas analysis, organizational document review, semi-structured interviews, Value-Focused Thinking, Focus Group Discussions, and the Simple Multi-Attribute Rating Technique (SMART). Interview data were analyzed using thematic content analysis supported by ATLAS.ti to derive evaluation criteria, while SMART analysis was used to compare four BPM tool alternatives: ARIS Express, Enterprise Architect Sparx, SAP Signavio, and Bizagi. Sensitivity analysis was conducted to test the robustness of the ranking results. The study identified six evaluation criteria: Cost, System Integration, System Security, Ease of Use, Feature Suitability, and Post-Implementation Support. Feature Suitability and System Security emerged as the most important criteria, followed by System Integration and Post-Implementation Support. The SMART results indicate that Enterprise Architect Sparx achieved the highest aggregate score and remained the top-ranked alternative across different sensitivity scenarios. This study contributes to BPM and digital transformation literature by positioning BPM tool selection as a governance-oriented strategic decision rather than a purely technical software evaluation. The proposed framework offers a structured decision-making approach for infrastructure enterprises, state-owned enterprise subsidiaries, and project-based organizations in emerging economies.